The efficiency of aspheric intraocular lens according to biometric measurements - Whang, Woong-Joo (PLoS One, 2017)
PURPOSE: To analyze internal spherical aberration in pseudophakic eyes that underwent aspheric intraocular lens (IOL) implantation, and to investigate the relationships between biometric data and the effectiveness of aspheric IOL implantation. METHODS: This retrospective study included 40 eyes of 40 patients who underwent implantation of an IOL having a negative spherical aberration of -0.20 μm (CT ASPHINA 509M; Carl Zeiss Meditec Inc., Germany). The IOLMaster (version 5.0; Carl Zeiss AG, Germany) was used for preoperative biometric measurements (axial length, anterior chamber depth, central corneal power) and the measurement of postoperative anterior chamber depth. The spherical aberrations were measured preoperatively and 3 months postoperatively using the iTrace (Tracey Technologies, Houston, TX, USA) at a pupil diameter of 5.0 mm. We investigated the relationships between preoperative biometric data and postoperative internal spherical aberration, and compared biometric measurements between 2 subgroups stratified according to internal spherical aberration (spherical aberration ≤ -0.06 μm vs. spherical aberration > -0.06 μm). RESULTS: The mean postoperative internal spherical aberration was -0.087 ± 0.063 μm. Preoperative axial length and residual total spherical aberration showed statistically significant correlations with internal spherical aberration (p = 0.041, 0.002). Preoperative axial length, postoperative anterior chamber depth, IOL power, and residual spherical aberration showed significant differences between the 2 subgroups stratified according to internal spherical aberration (p = 0.020, 0.029, 0.048, 0.041 respectively). CONCLUSION: The corrective effect of an aspheric IOL is influenced by preoperative axial length and postoperative anterior chamber depth. Not only the amount of negative spherical aberration on the IOL surface but also the preoperative axial length should be considered to optimize spherical aberration after aspheric IOL implantation.